Pengaruh Praktik Kerja Industri terhadap Kesiapan Kerja Siswa Smk Kota Jombang - Shanti Nugroho Sulistyowati; Sri Yuni Wulandari (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The unemployment rate in Jombang district is still quite high, data from the Central Statistics Agency for East Java Province shows that there are still 4.66 percent of Jombang residents who are still unemployed. Efforts to reduce the unemployment rate in the future are by preparing complex education and providing training. Prakerin is expected to be able to increase the work readiness attitude of vocational school students. The approach used in this research is quantitative, with the research population being class XII vocational school students in Jombang City who have taken part in Prakerin. The research results support the first hypothesis that the Prakerin variable has a positive and significant effect on the work readiness of vocational school students in the city of Jombang. It is shown in the f test where the significance value for the Prakerin variable (X) is 0.000 because the significance value <0.05 shows that there is a partial influence of the Prakerin variable (X) on the work readiness variable (Y).